The use of digital elevation model and GIS for geometric analysis of water reservoir to feed the hypothetical irrigation project west Makhoul in Salahuddin province - Rahman Hamoud Mudhi; Sabbar Abdullah Salih; Raad Hubei Arzouki (Tikrit Journal of Pure Science)
The reservoir under study is one of the basic components of the supposedly irrigation project, the geometric analysis of the reservoir was conducted, the geometric elements were extracted from the DEM, which are represented by the positive volume (the volume of islands), negative volume (volume of water storage), positive planner area (the projections of islands), negative planner area (area of evaporation), positive surface area (undulated surface of islands), negative surface area (bottom wetted area), average thickness of islands and the average of depth, at selected levels of the reservoir, the relations between geometric elements and water level, and geometric elements with each other, reveal that the positive volume and positive areas typically fluctuated with the changes of water level, because the immersion of islands and emergence of new other islands with the rising of levels, these elements are important for the future uses for these positive areas, as well as in the future maintain within the reservoir, and the way of movement between parts, and possible problems due to landslides from the positive parts towards the negative ones.